2023
DOI: 10.1292/jvms.22-0514
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal granulomas of basal ganglia due to <i>Cryptococcus neoformans</i> in a cat: a case report and literature review

Abstract: A 3-year-old spayed female domestic short-haired cat presented with a head turning to the left, circling to the right, seizures, and opisthotonos for approximately one month. Neurological examination revealed a deficit in the postural reaction of the left limbs and visual abnormalities. Forensic computed tomography revealed a hyperattenuating round mass of 1.3 cm diameter with a hypoattenuating center in the right hemisphere. Histopathology showed multifocal granuloma lesions with the major mass mostly affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In support, a cat with neurologic signs in Taiwan that underwent head CT and postmortem examination had multifocal cryptococcomas in the region of the basal ganglia with cryptococcal organisms in the Virchow-Robin (perivascular) spaces but without detectable sinonasal abnormalities. 15 In people, cryptococcal meningitis typically results from hematogenous dissemination from intrathoracic lesions and, very rarely, from abdominal structures such as the intestines. 2 The thorax was not routinely imaged in the present study to evaluate this possibility, although pulmonary cryptococcosis is reported infrequently in cats and dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support, a cat with neurologic signs in Taiwan that underwent head CT and postmortem examination had multifocal cryptococcomas in the region of the basal ganglia with cryptococcal organisms in the Virchow-Robin (perivascular) spaces but without detectable sinonasal abnormalities. 15 In people, cryptococcal meningitis typically results from hematogenous dissemination from intrathoracic lesions and, very rarely, from abdominal structures such as the intestines. 2 The thorax was not routinely imaged in the present study to evaluate this possibility, although pulmonary cryptococcosis is reported infrequently in cats and dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Sykes 6 described the MRI or CT findings in cats (n = 6) and dogs (9) from northern California with CNS cryptococcosis, while other reports document only 1 or 2 cases of CNS involvement in cats or dogs. 7,[10][11][12][13][14][15] In the California study, 6 MRI of the brain commonly showed multifocal or solitary parenchymal lesions that were hyperintense on T2-weighted (T2W) images, hypointense on T1-weighted (T1W) images, and variably contrast enhancing. These authors 6 suggested that cats with CNS infection tend to develop lesions consistent with gelatinous pseudocysts (T2 hyperintense but with more T1 intensity than expected for acellular fluid and only peripheral contrast enhancement), while dogs develop cryptococcal granulomas (more consistently contrast enhancing, with a marked inflammatory response in histopathological sections).…”
mentioning
confidence: 98%
“…A criptococose dever ser incluída no diagnóstico diferencial de outras doenças que causam sinais clínicos respiratórios e neurológicos (Huang et al, 2023), principalmente em animais imunodeprimidos associado a infecção pelo vírus da FeLV.…”
Section: Discussionunclassified